Monument culture international perspectives on the future of monuments in a changing world - Macaluso, Laura A. (American Association for State and Local History book series., 2019)
This book brings together a collection of essays from scholars and cultural critics working on the meanings of monuments and memorials in the second decade of the twenty-first century, a time of great social and political change.